Perancangan Jaket Menggunakan Material Limbah Benang dan Pakaian Bekas dengan Teknik Manipulasi Kain - Sumirat, Suci (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
In the ongoing era of the fashion industry, there are major challenges related to the environmental impact produced. One of the issues that needs to be resolved immediately is the problem of textile waste. This design aims to develop a jacket design that uses waste yarn and used clothes by applying fabric manipulation techniques. This design uses the design method of SP. Gustami's three-stage six-step design method. The process of this design is assisted by water soluble stabilizer as a thread stabilizer during the embroidery process. The results of this design are expected to be a guide in designing jackets that have high environmental value as well as attractive and creative designs. The design results of using waste yarn and used clothes as the main material in designing jackets can help reduce the amount of textile waste generated by the fashion industry. In addition, the fabric manipulation technique with embroidery also gives the jacket a creative touch and enhances the aesthetic value and uniqueness of the design. In conclusion, this research presents an innovative approach in jacket design by utilizing waste yarn and used clothing through the application of fabric manipulation techniques. By combining design creativity and textile waste utilization, this jacket can provide a sustainable solution in the fashion industry.